Impact of liver disease on oral anticoagulant prescription and major adverse events in patients with atrial fibrillation: analysis from a population-based cohort study. (25th November 2020) - Proietti, M; Marzona, I; Vannini, T; Colacioppo, P; Tettamanti, M; Foresta, A; Fortino, I; Merlino, L; Lip, G.Y.H; Roncaglioni, M.C
Abstract: Aims: Data on the impact of liver disease (LD) in patients with atrial fibrillation (AF) and the role of oral anticoagulant (OAC) drugs for stroke prevention, are limited. We analysed the impact of LD and OAC treatment in determining stroke, major bleeding, all-cause death and secondary bleeding outcomes. Methods: A retrospective observational population-based cohort study. The study cohort is derived from the administrative health databases of Lombardy region (>10 million inhabitants), Italy. All AF patients ≥40 years admitted to hospital from 2000 to 2018 were considered. AF and LD diagnosis were established using ICD9-CM codes. Use of OAC was determined with Anatomical Therapeutic Chemical (ATC) codes. Primary study outcomes were stroke, major bleeding and all-cause death. Results: Among 393, 507 AF patients, 16, 168 (4.1%) had concomitant LD. LD AF patients were significantly less treated with OAC independent of associated clinical characteristics (OR: 0.96, 95% CI: 0.92–0.98). Concomitant LD was found associated with an increased risk in all the study outcomes (HR: 1.18, 95% CI: 1.11–1.25 for stroke; HR: 1.57, 95% CI: 1.47–1.66 for major bleeding; HR: 1.41, 95% CI: 1.39–1.44 for all-cause death. Use of OAC in patients with AF and LD resulted in a reduction in stroke (HR: 0.80, 95% CI: 0.70–0.92), major bleeding (HR: 0.86, 95% CI: 0.74–0.99) and all-cause death (HR: 0.85, 95% CI: 0.80–0.90), with similar results according to several clinically relevant subgroups. A net clinical benefit (NCB) analysis suggested a positive benefit/risk ratio in using OAC in AF patients with LD (NCB: 0.408, 95% CI: 0.375–0.472). Conclusions: In AF patients, concomitant LD carries a significantly higher risk for all clinical outcomes. Use of OAC in AF patients with LD was associated with a significant benefit/risk ratio, even in high-risk patient subgroups. Funding Acknowledgement: Type of funding source: None